ENERGY AND EXERGY ANALYSES OF SELECTED TURKISH INDUSTRIES - ÖZDOĞAN, ZEYNEP SİBEL (PERGAMON-ELSEVIER SCIENCE LTD, 1995)
Analyses of the Turkish food, textile and cement sectors reveal that the most efficient sectors are different on energy and exergy bases. A quantitative break-down of exergy losses with respect to process heat, space and water heating, motive power, and illumination requirements indicates that exergy losses are mainly associated with space-, water- and process-heating. In the food and textile sectors, heating requirements with end-use temperatures below 200-degrees-C account for more than 90% of the total thermal energy demand. In the cement sector, however, low-temperature heat demand is almost negligible. Hence, measures to decrease the first-and second-law inefficiencies in these sectors may be drastically different.
Keywords: REQUIREMENTS